Multiple views system to support awareness for cooperative design. (June 2015) - Chen, Changyu; Zhao, Gang; Yu, Yong; Deng, Haiyan
Abstract: It is acknowledged that multiple views technology improves designer's work efficiency by filtering redundant information. However, the increased need of cooperative activities in product design process requires views incorporating Cooperative awareness information (CAI), content of which should be lean for understanding and sortable according to importance. To achieve this target, this paper proposes an Object-based cooperative awareness model (OBCWM) and corresponding multiple views system. Requirements of CAI in product design are firstly analyzed. Then OBCWM is proposed, which consists of a CPM (Core product model) based concept framework. By use of CPM, an algorithm to calculate awareness intensity is developed based on object-oriented method. To support the mechanism of OBCWM, a multiple views system is then designed with "flexible view", content of which is adjustable according to awareness intensity between CAI objects. After introduction to the system, application on a case is presented, followed by the evaluation of this system. Highlights: We devise a cooperative awareness model to describe cooperative awareness information in product design. We propose concept of awareness intensity and an object-oriented method to identify and filter overloaded cooperative awareness model. A mechanism which responds to changes of lean cooperative awareness information is proposed to plan and execute task in product design. A navigation net managed by a multiple views system is proposed to browser lean cooperative awareness information set.